Diagnosis of a Peritonsillar Abscess by Transcutaneous Point-of-Care Ultrasound in the Pediatric Emergency Department. Issue 7 (July 2016) - Halm, Brunhild M.; Ng, Carrie; Larrabee, Yuna C.
Abstract : Abstract: We report a case of a pediatric patient with an initial diagnosis of peritonsillar cellulitis made by otolaryngology. The findings from a subsequent transcutaneous point-of-care ultrasound by a pediatric emergency physician directly affected the decision to perform needle aspiration. Sonographic characteristics of a peritonsillar abscess may be helpful in the prompt diagnosis of peritonsillar abscess.